2018
DOI: 10.5194/angeo-36-489-2018
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations of thermospheric mass density at dawn/dusk from GOCE observations

Abstract: Abstract. Thermospheric mass densities from the GOCE (Gravity field and steady-state Ocean Circulation Explorer) satellite for Sun-synchronous orbits between 83.5 • S and 83.5 • N, normalized to 270 km during 2009-2013, have been used to develop an empirical mass density model at dawn/dusk local solar time (LST) sectors based on the empirical orthogonal function (EOF) method. The main results of this study are that (1) the dawn densities peak in the polar regions, but the dusk densities maximize in the equator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
2
7
0
Order By: Relevance
“…The year 1977 is chosen for simplicity to show qualitatively that anthropogenic cooling can cause some of the observed discrepancy. Additionally, comparisons of MSIS and GOCE densities at 250 km at the Dawn and Dusk terminators show GOCE measured densities to be ∼20% lower than those of MSIS from 2010 through 2013 (Weng et al., 2018). If absolute calibration differences between GOCE and MSIS are considered negligible, the lower GOCE densities are consistent with a cooler thermosphere than that predicted by MSIS.…”
Section: Discussionmentioning
confidence: 99%
“…The year 1977 is chosen for simplicity to show qualitatively that anthropogenic cooling can cause some of the observed discrepancy. Additionally, comparisons of MSIS and GOCE densities at 250 km at the Dawn and Dusk terminators show GOCE measured densities to be ∼20% lower than those of MSIS from 2010 through 2013 (Weng et al., 2018). If absolute calibration differences between GOCE and MSIS are considered negligible, the lower GOCE densities are consistent with a cooler thermosphere than that predicted by MSIS.…”
Section: Discussionmentioning
confidence: 99%
“…The density observations cover the time period from 1 November 2009 to 20 October 2013, and the orbital height varies from 230 to 280 km. To minimize the influence of orbital altitude variation, the GOCE density estimates have been normalized to a fixed altitude of 270 km by using the MSISE00 model (Weng et al, 2018). In this study, version 1.5 data for GOCE accelerometer-derived thermospheric total mass densities are utilized to conduct the density cell analysis.…”
Section: Methodsmentioning
confidence: 99%
“…They found that density cell structures in the lower thermosphere tend to occur in the local summer and the northern hemisphere, and that their local time distributions, horizontal scales, and relative magnitudes depend on the type of density cell structure. Weng LB et al (2018) further discussed the seasonal variations of lower thermospheric density by using GOCE satellite data and the Empirical Orthogonal Function method. They found that the seasonal density variations show obvious hemispheric asymmetry, with large amplitudes in the southern hemisphere, and that the annual asymmetry and effect of the Sun–Earth distance vary with latitude and solar activity.…”
Section: Ionospheric Dynamics and Couplingsmentioning
confidence: 99%